Severe Combined Immunodeficiency Disorders - Chinn, Ivan K; Shearer, William T (Immunology and allergy clinics of North America, 2015)
Severe combined immunodeficiency disorders represent pediatric emergencies due to absence of adaptive immune responses to infections. The conditions result from either intrinsic defects in T-cell development (ie, severe combined immunodeficiency disease [SCID]) or congenital athymia (eg, complete DiGeorge anomaly). Hematopoietic stem cell transplant provides the only clinically approved cure for SCID, although gene therapy research trials are showing significant promise. For greatest survival, patients should undergo transplant before 3.5 months of age and before the onset of infections. Newborn screening programs have yielded successful early identification and treatment of infants with SCID and congenital athymia in the United States.